All in the Family: By Michael Herb, Albany: State University New York Press, 1999, 351 pp. (American Journal of Islam and Society, 2000)
Despite the instability usually attributed to the Middle East, today one finds anunusual level of stability in eight of its monarchies. When mosl countries of theworld are converting to some form of "democracy," what has led this type ofstate system to such stability? In his book, All in the Family, Michael Herb,Assistant Professor of Political Science at Georgia State University, providesthe most thought-provoking work on Middle Eastern monarchies since rentierstate theory became fashionable. Herb determines that "there are two distinctforms of monarchism in the Middle East. One is resilient and the other is not''(p. 235). His basic thesis is that the key to the survival, persistence, andresilience of monarchies in the Middle East is the willingness and ability of theruling families to saturate the most important positions in the state apparatus.He terms this "dynastic monarchism"-the idea that "the ruling family formsitself into a ruling institution, monopolizing the key offices of the state" (p.235). In the unsuccessful type of monarchy, the king "maneuvers among variousforces-the army, the parliament, and the parties-and when he loses balancethe monarchy falls" (p. 235). Case studies are used to illustrate bothmonarchical models: dynastic (Kuwait, Saudi Arabia, Qatar, United ArabEmirates, Bahrain, and Oman) and nondynastic (Libya, Egypt, Iraq, Iran.Morocco, Jordan, and Afghanistan - usually excluded from studies on theMiddle East). This book relies on comparative analysis and is based not onlyon archival research, but also on interviews and secondary sources.In the second and third chapters, "The Emergence of Dynastic Monarchy andthe Causes of Its Persistence" and "Arabian Society and the Emergence of thePetro-State," respectively, the reader gets a sense of the rise of the petro-stateand how it enabled dynastic monarchies to emerge. He asserts that theyemerged because the ruler's relatives "had powerful bargaining resourceswhich they could use to help rulers stay in power, to aid aspiring rulers inachieving power, or to attack and depose sitting rulers" (p. 22). Tims, the emergenceof the petro-state added another dimension in intrafamily negotiations.Dynasties consolidate power by limiting the status of any individual or clique.Coalitions are built by the rulers through distribution of government positionsto relatives as a means of assuring their cooperation. Dynasties are strengthenedby forming consensus on the issue of succession rather than depending onprimogeniture. As a result, a ruler is held accountable to his family who ...